(untitled) (Journal of Mechanical Engineering, 2013)
The present numerical simulation has been conducted with the aim to observe the unsteady boundarylayer characteristics on a flat plate induced by a von Karman vortex street wake. This flow situation is anidealization of that occurring on turbomachinery blades where unsteady wakes are generated by the precedingrow of blades. In this research, the boundary layer is developed under zero pressure gradients while the vortexstreet is generated by an elliptic cylinder positioned in the free stream. The minor-major axes ratio of theelliptic cylinder is taken as 0.6 with an angle of attack 00. The investigation has been performed for differentcylinder-to-plate relative position and a Reynolds number of 500 based on the focal distance of the ellipticcylinder and free stream velocity. The time dependent, two dimensional flow is simulated numerically. Theconsequent mathematical model is governed by the coupled equations of mass, and momentum and solved byemploying Galerkin weighted residual method of finite element formulation. The development of the flow fieldup to certain time period is considered. Instantaneous streamlines of the disturbed flow field, instantaneousvelocity field, boundary layer integral parameters, and skin friction on different streamwise locations on theplate are presented in this paper. The result shows that the wake vortices strongly affect the boundary layerover the flat plate. DOI: http://dx.doi.org/10.3329/jme.v43i1.15771